Crop damage, autumn waterfowl populations and cereal grain harvests in the prairie provinces of western Canada - Clark, Robert G; Boyd, Hugh; Poston, Bert (Wildfowl, 1993)
We examined annual variations in cereal grain production, harvest chronology and waterfowl populations for the period 1978-87 in western Canada, testing whether damage to wheat and barley crops was affected most by speed of harvest, crop area and yield, Mallard and goose population levels, or a combination of these factors. Levels of damage (numbers of bushels lost or total compensation payments) were unrelated to seeded areas and yields of wheat or barley. Correlations between estimates of goose or Mallard abundance and crop damage were weak whereas those between damage and estimates of harvest delay were consistently much stronger. Numbers of feeding stations did not influence levels of crop damage recorded in Saskatchewan. Although cereal grain market value was associated with compensation paid to producers, the relationship differed from province to province. Overall, multivariate analyses that considered statistically all variables revealed, simultaneously, that delay in harvest was the most important factor affecting damage to cereal crops. Our results, based on the most reliable data available, were consistent with earlier reports and should help to dispel the perception held by many agricultural producers that crop damage levels are related directly to the size of waterfowl populations.